Aquatic Biodiversity II The Diversity of Aquatic Ecosystems - Segers, H.; Martens, K.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2005)
Freshwater Biodiversity is a much underestimated component of global biodiversity, both in its diversity and in its potential to act as models for fundamental research in evolutionary biology and ecosystem studies. Freshwater organisms also reflect quality of water bodies and can thus be used to monitor changes in ecosystem health. The present book comprises a unique collection of primary research papers spanning a wide range of topics in aquatic biodiversity studies, and including a first global assessment of specific diversity of freshwater animals. The book also presents a section on the interaction between scientists and science policy managers. A target opinion paper lists priorities in aquatic biodiversity research for the next decade and several reactions from distinguished scientists discuss the relevance of these items from different points of view: fundamental ecology, taxonomy and systematics, needs of developing countries, present-day biodiversity policy at European and at global scales. It is believed that such a platform for the interaction between science and science policy is an absolute necessity for the efficient use of research budgets in the future.
The study of biodiversity in freshwater habitats: societal relevance and suggestions for priorities in science policy -- Biodiversity: a resource with a monetary value? -- Linking science and policy for biodiversity -- Relevance and policy dimensions of research on biodiversity in freshwater ecosystems: a developing country perspective -- Conservation of freshwater biodiversity: does the real world meet scientific dreams? -- Taxonomy and systematics in biodiversity research -- Future priorities in science policy for biodiversity studies: a comment on the target review by Luc De Meester and Steven Declerck -- Towards a coherent and high-quality science policy on biodiversity -- An assessment of animal species diversity in continental waters -- Does inland aquatic biodiversity have a future in Asian developing countries? -- Recovery in diversity of fish and invertebrate communities following remediation of a polluted stream: investigating causal relationships -- Ecological remarks on Mastigodiaptomus nesus Bowman, 1986 (Copepoda: Calanoida) in a Mexican karstic sinkhole -- Consumptive and non-consumptive effects of turbellarian (Mesostoma sp.) predation on anostracans -- Changes in functional biodiversity in an invaded freshwater ecosystem: the Moselle River -- The impact of stocking on the genetic structure of European grayling (Thymallus thymallus, Salmonidae) in two alpine rivers -- Connectivity and nestedness of the meta-community structure of moss dwelling bdelloid rotifers along a stream -- Implications of taxonomic modifications and alien species on biological water quality assessment as exemplified by the Belgian Biotic Index method -- A large-scale stream benthic diatom database -- A review on the present status and management of mangrove wetland habitat resources in Bangladesh with emphasis on mangrove fisheries and aquaculture -- Coexistence of two similar copepod species, Eudiaptomus gracilis and E. graciloides: the role of differential predator avoidance -- Native and exotic Amphipoda and other Peracarida in the River Meuse: new assemblages emerge from a fast changing fauna -- Phylogeography and speciation in the Pseudocrenilabrus philander species complex in Zambian Rivers -- Short term spatial and temporal variation of phytoplankton in a shallow tropical oligotrophic reservoir, southeast Brazil -- The female reproductive organ in podocopid ostracods is homologous to five appendages: histological evidence from Liocypris grandis (Crustacea, Ostracoda) -- Daphnia species diversity in Kenya, and a key to the identification of their ephippia -- Some aspects of water filtering activity of filter-feeders -- Recent ostracods (Crustacea, Ostracoda) found in lowland springs of the provinces of Piacenza and Parma (Northern Italy) -- Representation of aquatic invertebrate communities in subfossil death assemblages sampled along a salinity gradient of western Uganda crater lakes -- Life history strategies of cladocerans: comparisons of tropical and temperate taxa -- Phylogeographic history of the genus Tropheus, a lineage of rock-dwelling cichlid fishes endemic to Lake Tanganyika -- Plankton richness in a eutrophic reservoir (Barra Bonita Reservoir, SP, Brazil) -- The effect of turbidity state and microhabitat on macroinvertebrate assemblages: a pilot study of six shallow lakes.
Keywords: Life sciences; Aquatic ecology .; Biodiversity; Ecosystems; Life Sciences, general; Freshwater & Marine Ecology; Biodiversity; Ecosystems